2017
DOI: 10.1097/ajp.0000000000000502
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Nerve Block as a Supplement to Light or Deep General Anesthesia in Elderly Patients Receiving Total Hip Arthroplasty

Abstract: Lumbosacral plexus block reduced the need for opioids and offered satisfactory postoperative analgesia. It led to better postoperative outcomes in combination with intraoperative light sedation (high bispectral index).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 37 publications
1
30
0
Order By: Relevance
“…All patients in the 3 groups received intubation. 26 Our study as a retrospective evaluation, lumbosacral plexus plus T 12 paravertebral nerve blocks without intubation were evaluated. The first RCT by Junfeng Zhang et al investigating the effect of combined lumbar and sacral plexus block with sedation versus general anesthesia on long-term prognosis indicated that ultrasound-guided combined lumbar and sacral plexus block with sedation could be safely used in hip fracture surgery in elderly patients and can reduce the incidence of perioperative complications and improve long-term prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…All patients in the 3 groups received intubation. 26 Our study as a retrospective evaluation, lumbosacral plexus plus T 12 paravertebral nerve blocks without intubation were evaluated. The first RCT by Junfeng Zhang et al investigating the effect of combined lumbar and sacral plexus block with sedation versus general anesthesia on long-term prognosis indicated that ultrasound-guided combined lumbar and sacral plexus block with sedation could be safely used in hip fracture surgery in elderly patients and can reduce the incidence of perioperative complications and improve long-term prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…67 Lumbosacral plexus block in combination with intraoperative light sedation resulted in better postoperative outcomes, reduced the use of opioids, and offered satisfactory postoperative analgesia. 72 Non-pharmaceutical management Acupuncture is an important method for POCD treatment. Liu et al showed that electroacupuncture intervention may improve cognitive function by inhibiting overexpression of the neuroinflammatory reaction and promoting improvement of neurological function.…”
Section: Pharmaceutical Managementmentioning
confidence: 99%
“…Both the combined lumbar and sacral plexus block (CLSB) with general anesthesia (BIS 60-80) and the unilateral spinal anesthesia (SA) on the operative side had been reported to be safe and effective as regional anesthesia techniques for hip surgery [9][10][11]. To the authors' knowledge, there were no studies comparing the superiority of these two anesthesia methods in terms of ADL.…”
Section: Introductionmentioning
confidence: 99%